Avaliation of the body condition score and famacha in suffolk ewes based pasture system (Research, Society and Development, 2022)
It is known that the cause of the greatest economic losses is worms in sheep production, in this way, integrated management can promote good performance in production and consequently generate less losses. Thus, the integrated handle can promote a good performance in production and consequently reduce the damages. This study aimed to evaluate the sanitary profile, through the association between the application of the FAMACHA method and the evaluation of the Body Condition Score (BCS), of Suffolk breed sheep in IFRS – Campus Sertão. The flock of 27 adult sheep were followed, totaling 725 evaluations in the year 2019. The FAMACHA method provided the reduction in expenses with anthelmintic drugs by 46.3% when compared to the traditional handle with two applications of anthelmintic drugs in sheep in the period analyzed. In the selective treatment, associated with BCS information and FAMACHA score, only 3.72% of the animals received anthelmintic drugs, while most of the flock with relatively few parasites or were able to support the parasite load without showing clinical signs. With the results, these sheep were classified into three groups into resistant, resilient and susceptible to verminosis. The study demonstrated the importance of zootechnical control and continuous monitoring of the flock, seeking to provide better productive and sanitary performance and consequently avoiding the indiscriminate use of anthelmintic drugs and improving the selection of animals.